2009
DOI: 10.1038/gt.2009.145
|View full text |Cite
|
Sign up to set email alerts
|

Dystrophin restoration in skeletal, heart and skin arrector pili smooth muscle of mdx mice by ZM2 NP–AON complexes

Abstract: Potentially viable therapeutic approaches for Duchenne muscular dystrophy (DMD) are now within reach. Indeed, clinical trials are currently under way. Two crucial aspects still need to be addressed: maximizing therapeutic efficacy and identifying appropriate and sensible outcome measures. Nevertheless, the end point of these trials remains painful muscle biopsy to show and quantify protein restoration in treated boys. In this study we show that PMMA/N-isopropilacrylamide+ (NIPAM) nanoparticles (ZM2) bind and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
35
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 17 publications
(22 reference statements)
2
35
0
Order By: Relevance
“…1c). We also analyzed sagittal cryosections from the brain, and, at all the stages analyzed, the fluorescence was exclusively localized in blood vessels and no signal was detectable in the nervous tissue and in the brain ventricles, demonstrating that ZM4 does not cross the blood-brain barrier.These results, together with the previous ones we reported on dystrophin restoration (Ferlini et al, 2010;Bassi et al, 2012), support the rationale of using NPs for AON delivery, even if improvements in biodegradability are needed. Moreover, our approach to profile biodistribution ''in vivo'' might be adopted also for other similar compounds.…”
supporting
confidence: 73%
See 2 more Smart Citations
“…1c). We also analyzed sagittal cryosections from the brain, and, at all the stages analyzed, the fluorescence was exclusively localized in blood vessels and no signal was detectable in the nervous tissue and in the brain ventricles, demonstrating that ZM4 does not cross the blood-brain barrier.These results, together with the previous ones we reported on dystrophin restoration (Ferlini et al, 2010;Bassi et al, 2012), support the rationale of using NPs for AON delivery, even if improvements in biodegradability are needed. Moreover, our approach to profile biodistribution ''in vivo'' might be adopted also for other similar compounds.…”
supporting
confidence: 73%
“…Our NPs bind 2¢OMePS oligoribonucleotides and have a functional effect, inducing body-wide dystrophin rescue both in skeletal and in cardiac muscles (Rimessi et al, 2009;Ferlini et al, 2010;Bassi et al, 2012). The main added value of using our NPs was related to the very-lowdose regimen of AONs able to restore dystrophin synthesis.…”
Section: Fig 1 (A)mentioning
confidence: 99%
See 1 more Smart Citation
“…For this application, that do not require the intervention of RNase-H, 2'OMe-RNA oligonucleotides are normally used, in the form of phosphorothioates (PS). Among other factors, the efficient delivery of the oligonucleotide remains a significant challenge for its use as therapeutic drugs, and we demonstrated that a possible solution was to convey the oligonucleotides across the cell membrane through the use of cationic core-shell nanoparticles [20,21].…”
Section: Exon Skippingmentioning
confidence: 99%
“…In this case, the uridine derivatives (20)(21)(22)(23) can be seen as conjugate nucleosides having an oligothiophene joined to the uridine base with a conductive linker. The formation of a hydrogen bonding following the correct pairing (U:dA) modifies the molecular orbitals of the uridine and of the conjugate label, resulting in a different fluorescence.…”
Section: Fluorescent Probesmentioning
confidence: 99%